2016
DOI: 10.18805/ijar.11467
|View full text |Cite
|
Sign up to set email alerts
|

Existing housing and breeding management practices adoptedby dairy farmers in Tarai region of Uttarakhand, India

Abstract: A field survey was conducted to collect the information on existing housing and breeding management practices followed by the dairy animal owners in Tarai region of Uttarakhand. The results revealed that 91.25 per cent of farmers adopted group housing system for their animals. Kuccha type of floor and asbestos roof was observed in 79.38 per cent and 26.25 per cent of animal houses respectively. Poor drainage facility was observed in 41.50 per cent of animal sheds. About, 89.38 per cent farmers provided their a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
0
1
Order By: Relevance
“…However, test of mastitis was done by dairy farms regularly in both the region. This finding is contrary to Tewari et al, (2018) who reported that majority of the farmers (60%) checked their animals for mastitis only when required. It indicates in present study that dairy farms were very aware and conscious about retrogressive effect of mastitis disease on economic output as well as production of animal.…”
Section: Milking Management Practicescontrasting
confidence: 80%
“…However, test of mastitis was done by dairy farms regularly in both the region. This finding is contrary to Tewari et al, (2018) who reported that majority of the farmers (60%) checked their animals for mastitis only when required. It indicates in present study that dairy farms were very aware and conscious about retrogressive effect of mastitis disease on economic output as well as production of animal.…”
Section: Milking Management Practicescontrasting
confidence: 80%